Predictors of fat oxidation and caloric expenditure with and without weighted vest running - Purdom, T. M.; Mermier, C.; Dokladny, K.; Moriarty, T.; Lunsford, L.; Cole, N.; Johnson, K.; Kravitz, L. (The Journal of Strength and Conditioning Research, 2021)
This study evaluated the effect of weighted vest running (WVR) on fatty acid oxidation (FAox) and caloric expenditure at predesignated steady-state exercise intensities. Seventeen recreationally trained runners (9 men and 8 women) performed 4 separate graded exercise tests (GXTs) separated by at least 24 hours. The first GXT was a V?o2max test to establish running velocities (percentage of max) at the prespecified exercise intensities (60, 65, 70, 75, and 80% V?o2max). The following randomized WVR trials included a control (no vest), 5% body mass (BM) vest, and 10% BM vest using 3-minute incrementally increasing steady-state stages. Indirect calorimetry was used to measure both FAox (g·min-1) and caloric expenditure (kcal·min-1) at each stage. The ANOVA/ANCOVA analysis revealed that intensity had the largest effect on and FAox (p < 0.001) while WVR had a significant main effect on both caloric expenditure and FAox (p < 0.05). Pairwise comparisons revealed that the 10% BM significantly increased caloric expenditure for all exercise intensities compared with control and 5% BM (except 60% V?o2max), while FAox decreased in the 10% BM 70 and 75% V?o2max intensities only. Marginal r-squared (R2m) demonstrate that when sex + fat-free mass (FFM) + fat mass (FM) were included as covariates, sex was a significant predictor of caloric expenditure but was further explained by the large FFM (kg) differences between the sexes significantly influencing caloric expenditure (R2m = 0.87, p < 0.001). Exercise intensity, body composition (FFM + FM), and external mass placement are relevant considerations for runners looking to maximize FAox and caloric expenditure.